Zeolite membrane composite, method for producing the same, and method for producing methanol using the same
Patent Information
- Application Number
- JP2025062566
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
AI Technical Summary
【0009】 本発明によれば、メタノールガス/水素ガスのパーミエンス比の高いゼオライト膜複合体、該ゼオライト膜複合体の製造方法、該ゼオライト膜複合体を用いたメタノールの製造方法を提供することができる。
Smart Images

Figure 2026168974000002 
Figure 2026168974000001
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a zeolite membrane composite and a method for producing methanol using the same for methanol separation.
BACKGROUND ART
[0002] Methods for producing methanol from a gas containing hydrogen and carbon monoxide (hereinafter sometimes referred to as "syngas") have been known for a long time, and examples thereof include methods using copper-based catalysts (copper-zinc based catalysts, copper-chromium based catalysts). The reaction for producing methanol from syngas is an equilibrium reaction, and is more favorable at lower temperatures and higher pressures. However, since the reaction rate decreases at lower temperatures, general methanol production processes are carried out under harsh conditions of 200 to 300°C and 5 to 10 MPaG (or higher pressures), which not only consumes a large amount of energy during methanol production, but also is a process with many facility-related restrictions.
[0003] As a method for efficiently producing methanol, a plurality of methods have been proposed in which methanol is removed from the reaction system to shift the gas composition in the reactor away from the equilibrium composition, and the reaction is carried out at a conversion rate exceeding the equilibrium conversion rate.
[0004] Further, Patent Documents 1 to 4 propose methods in which a separation membrane is installed in a methanol synthesis reactor, and methanol and water are removed from the reaction system using the separation membrane, so as to increase the conversion rate beyond the equilibrium conversion rate.
PRIOR ART DOCUMENTS
PATENT DOCUMENTS
[0005]
PATENT DOCUMENT 1
PATENT DOCUMENT 2
PATENT DOCUMENT 3
PATENT DOCUMENT 4
[0006] Patent Document 1 describes a lithium-ion-doped perfluorinated polysulfonic acid membrane as a methanol separation membrane. Patent Document 2 describes a porous graphite membrane, and Patent Document 3 describes a zeolite separation membrane of MFI type zeolite with a Si / Al ratio of 50 or more. Patent Document 4 describes preventing catalyst degradation by selectively removing water. However, while these methods were sufficient for separating carbon dioxide and methanol, separating hydrogen and methanol proved difficult, resulting in a low methanol / hydrogen gas permeance ratio, posing a challenge for further improvement. The inventors of the present invention investigated how to solve this problem by forming a dense, gapless film, but found that even when a sufficiently dense film was created, the permeance ratio was insufficient. Therefore, the object of the present invention is to provide a zeolite membrane composite with a high methanol gas / hydrogen gas permience ratio, a method for producing the zeolite membrane composite, and a method for producing methanol using the zeolite membrane composite. [Means for solving the problem]
[0007] To selectively permeate methanol gas while preventing the permeation of hydrogen gas, which has a small molecular size, it is effective to separate the gas by utilizing adsorption on a zeolite membrane. The inventors focused on the solid acidic properties of the zeolite membrane in order to enhance the interaction between methanol gas and the zeolite membrane and strengthen adsorption. They found that by heating the raw material mixture for hydrothermal synthesis at a low water concentration to promote the formation of a zeolite precursor, and then diluting it with water, the acidic properties of the zeolite membrane are enhanced, and the concentration of the raw material mixture becomes suitable for membrane formation. Zeolite membrane composites produced using this method were found to produce more carbon monoxide and carbon dioxide than zeolite membrane composites produced without this method, as measured by methanol thermal desorption gas mass spectrometry. Zeolite membrane composites that produce more carbon monoxide and carbon dioxide exhibit stronger adsorption of methanol, a polar molecule, inhibiting the permeation of gases other than methanol and improving the methanol gas / hydrogen gas permeation ratio. This led to the present invention.
[0008] The present invention is as follows: [1] A zeolite membrane composite having a zeolite membrane on a porous support, wherein the total amount of carbon monoxide and carbon dioxide generated by methanol thermal desorption gas mass spectrometry at 100°C to 800°C, calculated using nitrogen sensitivity, is 6.2 μmol / g or more. [2] The zeolite membrane composite according to [1] above, wherein the zeolite is of the MFI type. [3] The zeolite membrane composite according to [1] or [2] above, wherein the Si / Al molar ratio of the zeolite membrane is 5.0 or more and 25.0 or less. [4] A method for producing a zeolite membrane composite, using a hydrothermal synthesis raw material mixture prepared by a method comprising: a first step of preparing a mixture containing at least aluminum atom raw materials, alkali metal atom raw materials, and water; a second step of mixing silicon atom raw materials; a third step of heating the mixture after the second step at 40°C or higher; and a fourth step of mixing water with the mixture after heating in the third step. [5] The method for producing a zeolite membrane composite according to [4] above, wherein the water content of the mixture prepared by the first step is 30% or more and 80% or less of the amount of water in the hydrothermal synthesis raw material mixture. [6] A method for producing methanol, comprising reacting a raw material gas containing at least hydrogen and carbon monoxide and / or carbon dioxide in a reactor in the presence of a catalyst, wherein the methanol produced by the reaction is extracted by permeating through a zeolite membrane composite according to any one of [1] to [3] above. [Effects of the Invention]
[0009] According to the present invention, it is possible to provide a zeolite membrane composite with a high methanol gas / hydrogen gas permience ratio, a method for producing the zeolite membrane composite, and a method for producing methanol using the zeolite membrane composite. [Brief explanation of the drawing]
[0010] [Figure 1] Figure 1 is an explanatory diagram illustrating an example of a method for producing methanol using the zeolite membrane composite of the present invention. [Modes for carrying out the invention]
[0011] The following describes typical embodiments for carrying out the present invention, but the present invention is not limited to the following embodiments as long as it does not exceed its gist, and can be implemented in various modified forms.
[0012] The zeolite membrane composite according to an embodiment of the present invention has a zeolite membrane on a porous support, and the total amount of carbon monoxide and carbon dioxide generated, calculated using methanol thermal desorption gas mass spectrometry at a nitrogen sensitivity of 100°C to 800°C, is 6.2 μmol / g or more.
[0013] The methanol temperature-induced desorption gas mass spectrometry method of the present invention involves, as a pretreatment, temperature-induced desorption of water molecules and the like adsorbed on a zeolite membrane composite, followed by the introduction of methanol gas and its adsorption onto the zeolite membrane composite. For the pretreatment, the temperature and time for temperature-induced desorption should be sufficient to remove water molecules and the like, and the temperature and time for methanol gas introduction should be sufficient to adsorb methanol gas.
[0014] After pretreatment, the system is held at 100°C for 10 minutes while the carrier gas is kept flowing, and then the temperature is raised to 800°C at a rate of 10°C / min. The generated gas during this process is introduced into the ionization unit of a mass spectrometer, ionized by the EI method, and analyzed with a time-of-flight mass spectrometer.
[0015] The total amount of generated carbon monoxide and carbon dioxide converted by nitrogen sensitivity from 100°C to 800°C in the methanol temperature-programmed desorption gas mass spectrometry method of the present invention is 6.2 μmol / g or more from the viewpoint of enhancing the acid properties of the zeolite membrane composite, preferably 6.5 μmol / g or more, and more preferably 7.0 μmol / g or more. In addition, the upper limit is preferably 30.0 μmol / g or less, more preferably 25.0 μmol / g or less, and even more preferably 20.0 μmol / g or less, from the viewpoint of preventing deterioration of methanol gas due to excessive oxidizing ability.
[0016] The amount of generated carbon monoxide converted by nitrogen sensitivity from 100°C to 800°C in the methanol temperature-programmed desorption gas mass spectrometry method of the present invention is preferably 1.3 μmol / g or more, more preferably 1.4 μmol / g or more, and even more preferably 1.5 μmol / g or more. The upper limit is not particularly limited, but is preferably 15.0 μmol / g or less, more preferably 10.0 μmol / g or less, and even more preferably 7.0 μmol / g or less.
[0017] The amount of generated carbon dioxide converted by nitrogen sensitivity from 100°C to 800°C in the methanol temperature-programmed desorption gas mass spectrometry method of the present invention is preferably 5.2 μmol / g or more, more preferably 5.5 μmol / g or more, and even more preferably 6.0 μmol / g or more. The upper limit is not particularly limited, but is preferably 20.0 μmol / g or less, more preferably 15.0 μmol / g or less, and even more preferably 10.0 μmol / g or less.
[0018] The standard measurement method for methanol-temperature desorbed gas mass spectrometry according to the present invention, as used in the analysis of the examples, is shown below.
[0019] (Device) Equipment name: JEOL time-of-flight mass spectrometer JMS-T200GC AccuTOF GCx
[0020] (Pre-processing) Pretreatment temperature: 300℃ Heating rate: 10°C / min Pre-processing time: 30 minutes Methanol introduction method: Underflow Methanol introduction start temperature (holding temperature during methanol introduction): 100℃ Methanol flow time: 25 minutes
[0021] (Measurement conditions) Measurement start temperature: 100℃ Starting temperature holding time: 10 minutes Target temperature: 800℃ Heating rate: 10°C / min Target temperature holding time: 0 minutes Carrier gas: Helium (G1 grade) mixed with argon at a pressure of 0.05 MPa or less. The amount of oxygen from air mixed into the carrier gas should be 50 ppm or less. Flow rate: 40mL / min
[0022] (Analysis method) Each data point is normalized using the intensity of argon in the carrier gas as an indicator to ensure consistent sensitivity for each measurement before being subjected to analysis. The ion current chromatogram at m / z:27.99 is considered to be derived from carbon monoxide, and the ion current chromatogram at m / z:44 is considered to be derived from carbon dioxide. The ion current chromatograms derived from carbon monoxide and carbon dioxide in each sample are normalized by the sample volume. Subsequently, the peak intensities are calculated from 10 minutes of holding time to 800°C (70 minutes). Then, the amount of carbon monoxide and carbon dioxide generated is calculated by applying the relationship between the amount of substance and peak area obtained by pulse-introducing atmospheric nitrogen using a gas-tight syringe. As described above, by normalizing the data using argon in the carrier gas as an indicator and then converting it from the nitrogen sensitivity, the daily error can be suppressed, and the amount of gas generated per unit weight of sample can be easily calculated and compared.
[0023] [Zeolite membrane complex] The zeolite membrane composite of the present invention has a zeolite membrane on a porous support.
[0024] <Porous support> The porous support used in the present invention can be made of various materials, but is preferably an inorganic porous material. Specific materials that can be used include alumina, titania, zirconia, and silica, but is preferably alumina. Regarding the pores of the porous support, there are no particular limitations as long as macropores are present and do not prevent the zeolite membrane from forming properly; commonly used materials can be used.
[0025] <Zeolite membrane> The zeolite used to constitute the zeolite film in the present invention is not particularly limited as long as it contains aluminum, but the main zeolite constituting the zeolite film is preferably one that contains zeolites having pores with 12 or fewer oxygen rings and 6 or more oxygen rings. In this context, the value of n in zeolites having an n-membered oxygen ring indicates the pore with the largest number of oxygen atoms among the pores composed of oxygen and T elements (elements other than oxygen that make up the zeolite framework). For example, if pores with both 12-membered and 8-membered oxygen rings exist, as in MOR-type zeolites, it is considered a zeolite with a 12-membered oxygen ring.
[0026] Zeolites having a pore structure with 12 or fewer oxygen rings and 6 or more oxygen rings are defined by the International Zeolite Association (IZA) as follows, for example, AEI, AEL, AFI, AFG, ANA, ATO, BEA, BRE, CAS, CDO, CHA, CON, DDR, DOH, EAB, EPI, ERI, ESV, EUO, FAR, FAU, FER, FRA, HEU, GIS, GIU, GME, GOO, ITE, KFI, LEV, LIO, LOS, LTA, LTL, LTN, MAR, MEP, MER, MEL, MFI, MON, MOR, MSO, MTF, MTN, MTW, MWW, NON, NES, OFF, PAU, PHI, RHO, RTE, RTH, RUT, SGT, OD, STI, STT, TOL, TON, TSC, UFI, VNI, WEI, YUG, etc. It is preferable that it be one of these selected options. More preferably, it is one of the CHA type, FAU type, MFI type, LTA type, or RHO type, even more preferably CHA type, MFI type, LTA type, or RHO type, even more preferably MFI type or RHO type, and most preferably MFI type.
[0027] The Si / Al molar ratio of the zeolite film according to this embodiment is preferably 5.0 to 25.0, more preferably 7.0 to 20.0, and even more preferably 9.0 to 15.0. Because some of the Si atoms, which are T atoms constituting the zeolite framework, are replaced by Al atoms, solid acid sites are formed where protons or sodium ions are adsorbed due to charge compensation. These solid acid sites can strongly adsorb methanol gas, a polar molecule, contributing to preferential permeability for gas separation applications. It is desirable to have as many Al atoms as possible, i.e., a low Si / Al molar ratio. On the other hand, introducing too many Al atoms into the zeolite framework may lead to a decrease in crystallinity and the formation of defects.
[0028] The thickness of the zeolite film is not particularly limited, but is preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 2 μm or more. This lower limit allows the film to perform well as a separation membrane. The upper limit of the film thickness is preferably 30 μm or less, more preferably 20 μm or less, and most preferably 10 μm or less. This upper limit prevents damage to the zeolite film due to thermal expansion, while simultaneously obtaining sufficient transmittance. The film thickness can be easily distinguished by the difference in density between the zeolite portion and the support portion using SEM, and can be measured by measuring several average locations using SEM observation. It is sufficient to measure five average locations and take the average value, preferably all five locations falling within the aforementioned range.
[0029] The zeolite membrane composite of the present invention relieves stress caused by thermal expansion and suppresses the occurrence of peeling and cracking of the zeolite membrane, and therefore exhibits its effects without limiting its applications. However, it is particularly effective when used at temperatures higher than room temperature, and is preferably applied to applications where it is used at 70°C or higher. As will be described later as an example of its application to a methanol production method, it can also be suitably used for the separation of ammonia and other substances.
[0030] <Method for producing zeolite membrane composites> Next, the method for producing the zeolite membrane composite of the present invention will be described. The present invention provides a method for producing a zeolite membrane composite using a commonly used method for producing a zeolite membrane on a general porous material. Methods for supporting the zeolite membrane include dipping, rubbing, suction, and impregnation. It is preferable to use microcrystals called seed crystals. These seed crystals serve as nuclei for growing the crystals that constitute the zeolite membrane.
[0031] In the method for producing a zeolite membrane composite according to the embodiment of the present invention, it is preferable to use a hydrothermal synthesis raw material mixture prepared by a method comprising: a first step of preparing a mixture containing at least aluminum atom raw material, alkali metal atom raw material, and water; a second step of mixing in silicon atom raw material; a third step of heating the mixture after the second step at 40°C or higher; and a fourth step of mixing water with the mixture after heating in the third step.
[0032] In the first step, a mixture containing at least an aluminum atom raw material, an alkali metal atom raw material, and water is prepared. The aluminum atom raw material is not particularly limited and includes aluminosilicate zeolite, amorphous aluminum hydroxide, aluminum hydroxide with a gibbsite structure, aluminum hydroxide with a bayerite structure, aluminum nitrate, aluminum sulfate, aluminum oxide, sodium aluminate, boehmite, pseudoboehmite, aluminum alkoxide, and aluminosilicate gel. Aluminosilicate zeolite, amorphous aluminum hydroxide, sodium aluminate, boehmite, pseudoboehmite, aluminum alkoxide, and aluminosilicate gel are preferred, and aluminosilicate zeolite, amorphous aluminum hydroxide, sodium aluminate, and aluminosilicate gel are particularly preferred. These may be used individually or in combination of two or more.
[0033] Examples of alkali metal atoms include Li, Na, K, Rb, Cs, and two or more of these metal atoms. Among these, Li, Na, and Cs are preferred because they exhibit excellent ammonia separation performance and are general-purpose alkali metals. Na is more preferred as the alkali metal atom raw material. The raw material is not particularly limited, and alkali metal hydroxides, alkali metal chlorides, etc., can be used. The metal species of these metal hydroxides are usually sodium (Na), potassium (K), lithium (Li), preferably Na and K, and more preferably Na. Furthermore, one metal species of metal oxide may be used alone, or two or more may be used in mixture form.
[0034] Each material can be mixed together by stirring. The stirring method is not particularly limited, but a three-in-one motor with stirring blades or a magnetic stirrer is preferred because it increases the solubility of the raw materials. To avoid changes in concentration due to the evaporation of water, it is desirable to mix in a closed system, and an air or nitrogen atmosphere is preferred.
[0035] In the second step, silicon atom raw materials are mixed with the mixture prepared in the first step. The silicon atom raw materials are not particularly limited, but examples include aluminosilicate zeolite, fumed silica, colloidal silica, amorphous silica, sodium silicate, methyl silicate, ethyl silicate, silicon alkoxides such as trimethylethoxysilane, tetraethyl orthosilicate, and aluminosilicate gel. Preferably, aluminosilicate zeolite, fumed silica, colloidal silica, amorphous silica, sodium silicate, methyl silicate, ethyl silicate, silicon alkoxide, and aluminosilicate gel are used. These may be used individually or in combination of two or more.
[0036] In the third step, the mixture from the second step is heated to 40°C or higher. The heating temperature is preferably 45°C or higher, and more preferably 50°C or higher. To avoid changes in concentration due to water evaporation, it is desirable to mix in a closed system, and an air or nitrogen atmosphere is preferred.
[0037] In the fourth step, water is mixed with the mixture after heating in the third step. By mixing in water, a raw material mixture for hydrothermal synthesis can be obtained.
[0038] In the method for producing a zeolite membrane composite according to an embodiment of the present invention, the water content of the mixture prepared in the first step is preferably 30% to 80%, more preferably 35% to 70%, and even more preferably 40% to 60% of the water content of the hydrothermal synthesis raw material mixture. By using the above ratios, it is possible to promote the generation of precursors that contribute to the formation of the zeolite skeleton while maintaining fluidity suitable for mixing.
[0039] The present invention provides a method for producing a zeolite membrane composite, for example, by vertically immersing four porous supports, each with attached seed crystals, in a pressure vessel containing a mixture of raw materials for hydrothermal synthesis, sealing the vessel, and heating it in a constant temperature bath. At this time, from the viewpoint of promoting the crystallization of the zeolite membrane, the heating temperature is preferably 140°C or higher, more preferably 160°C or higher, and even more preferably 180°C or higher. From the viewpoint of avoiding weakening due to dissolution of the porous supports and the generation of impurity phases, the temperature is preferably 240°C or lower, more preferably 220°C or lower, and even more preferably 200°C or lower.
[0040] <Method for producing methanol> The methanol production method according to this embodiment is a methanol production method in which a raw material gas containing at least hydrogen and carbon monoxide and / or carbon dioxide is reacted in a reactor in the presence of a catalyst to obtain methanol, wherein the methanol produced by the reaction is extracted by permeating through a zeolite membrane composite. The raw gases are H2 and CO2. x It may contain other gases besides H2 and CO2. x Other gases include CH4, C2H4, C2H6, C3H6, C3H8, C4H8, and C4H 10 Examples include H2O, but H2 and CO x The content of other gases is usually 50% by volume or less.
[0041] When producing methanol from a raw material gas, known catalysts can be used, such as copper-based catalysts (copper-zinc catalysts, copper-chromium catalysts), zinc-based catalysts, chromium-based catalysts, and aluminum-based catalysts.
[0042] A zeolite membrane composite can be formed by, for example, preparing a cylindrical support, first supporting zeolite microcrystals within the pores, and then forming a zeolite membrane on the support. Hydrothermal synthesis can be used for zeolite growth, similar to zeolite synthesis. In this embodiment, the zeolite membrane composite described above can be used.
[0043] Figure 1 is a schematic cross-sectional view showing one embodiment of a reactor in which the present invention is implemented. Reactor 10 has a raw material feed inlet a, a permeate gas outlet b, and a non-permeate gas outlet c, and is made of a material that can withstand the high temperature and pressure environment in which the methanol production reaction takes place. In the figure there is only one inlet a, one outlet b, and one outlet c, but there may be multiple inlets a, one outlet b, and one outlet c. For example, the zeolite membrane composite 1 of the present invention is installed inside the reactor 10.
[0044] The zeolite membrane composite 1 is formed when a zeolite membrane is formed on a porous support. The shape of the porous support is not limited to tubular, but may be columnar, hollow columnar, or hollow honeycomb. One end of the zeolite membrane composite 1 is sealed by a cap 2, and the other end is connected to a pipe 3. The connection between the pipe 3 and the zeolite membrane composite 1, and the connection between the cap 2 and the zeolite membrane composite 1, is made by a bonding material. The method of connecting the zeolite membrane composite 1 is not limited to the above; for example, both ends may be connected to a pipe, allowing gas to flow inside.
[0045] A catalyst 13 is arranged around the tubular zeolite membrane complex 1. The raw material gas fed from the feed inlet a has methanol production promoted through contact with the catalyst 13. The generated methanol then permeates through the zeolite membrane of the zeolite membrane complex 1, allowing for the production of higher purity methanol. Furthermore, the selective permeation of methanol through the zeolite complex 1 reduces the methanol concentration in the gas in contact with the catalyst 13, thereby promoting methanol production.
[0046] The other end of piping 3 is connected to the permeate gas outlet b of the reactor, transferring methanol that has permeated through the zeolite membrane of the zeolite membrane complex 1 to the permeate gas outlet b. Alternatively, the zeolite membrane complex 1 may be connected directly to the permeate gas outlet b of the reactor without going through piping 3.
[0047] The reaction conditions are not particularly limited, but the reaction temperature is preferably between 200°C and 300°C. Note that the reaction temperature refers to the temperature inside the reactor. A reaction temperature of 200°C or higher increases the reaction rate and improves productivity. A reaction temperature of 300°C or lower creates a chemical equilibrium that is favorable for obtaining methanol, allowing for a higher conversion rate even if the film performance is somewhat inferior. Furthermore, the acceptable range of heat resistance required for the bonding material is also broadened.
[0048] The methanol obtained from the above reaction permeates through the zeolite membrane complex in the reactor, and the methanol is recovered from the permeate gas outlet of the reactor. The pressure inside the reactor when the generated methanol is permeated through the zeolite membrane composite, i.e., the pressure (gauge pressure) on the gas supply side of the zeolite membrane composite inside the reactor, is preferably 1 MPaG or higher, more preferably 2 MPaG or higher, preferably 8 MPaG or lower, and more preferably 5 MPaG or lower. By setting the pressure within an appropriate range, the equilibrium constraints of the reaction are reduced, and the reaction rate is improved, making it easier to achieve higher productivity. In addition, the increase in reactor manufacturing costs and raw material gas pressurization costs due to excessively high pressure can be suppressed. Furthermore, within the reaction vessel, the methanol partial pressure (absolute pressure) on the gas supply side of the zeolite membrane composite is preferably 0.1 MPaA or higher, more preferably 0.2 MPaA or higher, preferably 6 MPaA or lower, and more preferably 5 MPaA or lower. By setting the methanol partial pressure within this range, a sufficient amount of methanol permeates the membrane, and the membrane's effect is fully realized. On the other hand, within this range, the required durability and sealing performance of the joints do not become unnecessarily high, and joining can be done simply and in large quantities. The gauge pressure inside the reactor can be measured using a pressure gauge installed in the reactor. Furthermore, while the absolute pressure of methanol inside the reactor changes from upstream to downstream, here we will use the value calculated from the analysis results of the reactor outlet gas composition by gas chromatography and the gauge pressure as the absolute pressure of methanol inside the reactor. [Examples]
[0049] The present invention will be described in more detail below with reference to examples, but it goes without saying that the scope of the present invention is not limited to the embodiments shown in the following examples.
[0050] <Example 1> (Raw material mixture for hydrothermal synthesis) 2.1 g of 99% by mass sodium hydroxide (manufactured by Kishida Chemical Co., Ltd., pelletized) and 45.5 g of desalinated water were mixed, and 0.18 g of sodium aluminate (manufactured by Kishida Chemical Co., Ltd., containing 62.2% by mass Al2O3) was added and the mixture was stirred at 50°C for 30 minutes. 27.3 g of colloidal silica (manufactured by Nissan Chemical Corporation, Snowtex XS) was added to this mixture and stirred at 50°C for 2 hours. After that, 100.6 g of desalinated water was added to prepare the raw material mixture for hydrothermal synthesis. The composition (molar ratio) of this raw material mixture for hydrothermal synthesis was SiO2 / Al2O3 / NaOH / H2O = 1 / 0.012 / 0.62 / 100.
[0051] (Porous support) As the porous support, we used an 8cm alumina tube (outer diameter 12mm, inner diameter 9mm) manufactured by Iwao Porcelain Industry Co., Ltd., which was washed with desalinated water and then dried.
[0052] (Seed crystal dispersion) A seed crystal dispersion was prepared by grinding MFI-type zeolite (Na type, Si / Al molar ratio = 108, Na / Al molar ratio = 1.74) in a mortar and pestle, and then dispersing the seed crystals in water to a concentration of 0.15% by mass.
[0053] (Manufacturing of zeolite membrane composites) The porous support was immersed in the seed crystal dispersion described above for 20 seconds, then dried at room temperature for 30 minutes and at 70°C for 30 minutes to allow the seed crystals to adhere to the porous support. The excess seed crystals that had adhered were polished off with a rubber plate, and the mass of the removed seed crystals was approximately 0.0041 g. Three porous supports with attached seed crystals were prepared using this method. Three porous supports with seed crystals attached were immersed vertically in a Teflon® inner cylinder containing the above-mentioned hydrothermal synthesis raw material mixture. The autoclave was sealed, and the temperature was raised to 180°C in a constant temperature bath over 5 hours, followed by 15 hours of standing heating under self-synthesis pressure. After the predetermined time had elapsed, the porous support-zeolite membrane composite was allowed to cool, removed from the reaction mixture, washed, and then immersed again in demineralized water at 90°C for 30 minutes. After 30 minutes, the zeolite membrane composite was removed from the demineralized water. Using fresh demineralized water at 90°C, the immersion and removal operations were repeated a total of four times. The porous support-zeolite membrane composite was then dried at 100°C for 1 hour to obtain MFI-type zeolite membrane composite 1. The results of methanol temperature-induced desorption gas mass spectrometry of this zeolite membrane composite are shown in Table 1. The mass of the zeolite membrane on the porous support was 0.078 g. Furthermore, a mixed gas of methanol (MeOH) and hydrogen (H2) was separated using a zeolite membrane composite, and the permeance (transmission rate) of each was measured, and the permeance ratio was calculated. The results are shown in Table 1. The air permeability of the zeolite membrane composite at 50 Torr is 0.9 cm³. 3 It was / minutes.
[0054] <Example 2> (Raw material mixture for hydrothermal synthesis) 2.1 g of 99% by mass sodium hydroxide (Kishida Chemical Co., Ltd., pelletized) and 45.5 g of desalinated water were mixed, and 0.18 g of sodium aluminate (Kishida Chemical Co., Ltd., containing 62.2% by mass Al2O3) was added and the mixture was stirred at 70°C for 30 minutes. 27.3 g of colloidal silica (Nissan Chemical Co., Ltd., Snowtex XS) was added to this mixture and stirred at 70°C for 2 hours. After that, 100.6 g of desalinated water was added to prepare the raw material mixture for hydrothermal synthesis. The composition (molar ratio) of this raw material mixture for hydrothermal synthesis was SiO2 / Al2O3 / NaOH / H2O = 1 / 0.012 / 0.62 / 100.
[0055] (Porous support) As the porous support, we used an 8cm alumina tube (outer diameter 12mm, inner diameter 9mm) manufactured by Iwao Porcelain Industry Co., Ltd., which was washed with desalinated water and then dried.
[0056] (Seed crystal dispersion) A seed crystal dispersion was prepared by grinding MFI-type zeolite (Na type, Si / Al molar ratio = 108, Na / Al molar ratio = 1.74) in a mortar and pestle, and then dispersing the seed crystals in water to a concentration of 0.15% by mass.
[0057] (Manufacturing of zeolite membrane composites) The porous support was immersed in the seed crystal dispersion described above for 25 seconds, then dried at room temperature for 30 minutes and at 70°C for 30 minutes to allow the seed crystals to adhere to the porous support. The excess seed crystals were polished off with a rubber plate, and the mass of the removed seed crystals was approximately 0.0040 g. Three porous supports with attached seed crystals were prepared using this method. Three porous supports with seed crystals attached were each immersed vertically in a Teflon® inner cylinder containing the above-mentioned hydrothermal synthesis raw material mixture. The autoclave was sealed, and the temperature was raised to 180°C in a constant temperature bath over 5 hours, followed by 15 hours of standing heating under self-synthesis pressure. After the predetermined time had elapsed, the porous support-zeolite membrane composite was allowed to cool, removed from the reaction mixture, washed, and then immersed again in 90°C demineralized water for 30 minutes. After 30 minutes, the zeolite membrane composite was removed from the demineralized water. Using fresh 90°C demineralized water, the immersion and removal operations were repeated a total of four times. The porous support-zeolite membrane composite was then dried at 100°C for 1 hour to obtain MFI-type zeolite membrane composite 2. The results of methanol temperature-induced desorption gas mass spectrometry of this zeolite membrane composite are shown in Table 1. The mass of the zeolite membrane on the porous support was 0.072 g. Furthermore, a mixed gas of methanol (MeOH) and hydrogen (H2) was separated using a zeolite membrane composite, and the permeance (transmission rate) of each was measured, and the permeance ratio was calculated. The results are shown in Table 1. The air permeability of the zeolite membrane composite at 50 Torr is 0.3 cm³. 3 It was / minutes.
[0058] <Comparative Example 1> (Raw material mixture for hydrothermal synthesis) 2.1 g of 99% by mass sodium hydroxide (manufactured by Kishida Chemical Co., Ltd., pelletized) and 146.1 g of desalted water were mixed, and 0.12 g of sodium aluminate (manufactured by Kishida Chemical Co., Ltd., containing 62.2% by mass Al2O3) was added and the mixture was stirred at 50°C for 30 minutes. 27.3 g of colloidal silica (manufactured by Nissan Chemical Corporation, Snowtex XS) was added to this mixture and stirred at 50°C for 2 hours to obtain a hydrothermal synthesis raw material mixture. The composition (molar ratio) of this hydrothermal synthesis raw material mixture was SiO2 / Al2O3 / NaOH / H2O = 1 / 0.008 / 0.62 / 100.
[0059] (Porous support) As the porous support, we used an 8cm alumina tube (outer diameter 12mm, inner diameter 9mm) manufactured by Iwao Porcelain Industry Co., Ltd., which was washed with desalinated water and then dried.
[0060] (Seed crystal dispersion) A seed crystal dispersion was prepared by grinding MFI-type zeolite (Na type, Si / Al molar ratio = 108, Na / Al molar ratio = 1.22) in a mortar and pestle, and then dispersing the seed crystals in water to a concentration of 0.15% by mass.
[0061] (Manufacturing of zeolite membrane composites) The porous support was immersed in the seed crystal dispersion described above for 30 seconds, then dried at room temperature for 30 minutes and at 70°C for 30 minutes to allow the seed crystals to adhere to the porous support. The excess seed crystals were polished off with a rubber plate, and the mass of the removed seed crystals was approximately 0.0042 g. Three porous supports with attached seed crystals were prepared using this method. Three porous supports with seed crystals attached were each immersed vertically in a Teflon® inner cylinder containing the above-mentioned hydrothermal synthesis raw material mixture. The autoclave was sealed, and the temperature was raised to 180°C in a constant temperature bath over 5 hours, followed by 15 hours of standing heating under self-synthesis pressure. After the predetermined time had elapsed, the porous support-zeolite membrane composite was allowed to cool, removed from the reaction mixture, washed, and then immersed again in demineralized water at 90°C for 30 minutes. After 30 minutes, the zeolite membrane composite was removed from the demineralized water. Using fresh demineralized water at 90°C, the immersion and removal operations were repeated a total of four times, and then the porous support-zeolite membrane composite was dried at 100°C for 1 hour to obtain MFI-type zeolite membrane composite 3. The results of methanol desorption gas mass spectrometry of this zeolite membrane composite are shown in Table 1. The mass of the zeolite membrane on the porous support was 0.082 g. Furthermore, a mixed gas of methanol (MeOH) and hydrogen (H2) was separated using a zeolite membrane composite, and the permeance (transmission rate) of each was measured, and the permeance ratio was calculated. The results are shown in Table 1. The air permeability of the zeolite membrane composite at 50 Torr is 0.2 cm³. 3 It was / minutes.
[0062] [Table 1] [Industrial applicability]
[0063] It has been revealed that a high methanol gas / hydrogen gas permeance ratio can be obtained when producing methanol using the zeolite membrane composite of the present invention. Furthermore, since the principle by which this high permeance is obtained is common to other reactions as well, it can be applied to various reactions requiring separation, and as a zeolite separation membrane that can obtain high permeance, it is a technology with high industrial value. [Explanation of Symbols]
[0064] 1. Zeolite membrane complex 2 caps 3 Piping 10 Reactors 13 Catalyst
Claims
1. A zeolite membrane composite having a zeolite membrane on a porous support, wherein the total amount of carbon monoxide and carbon dioxide generated by methanol thermal desorption gas mass spectrometry at 100°C to 800°C, calculated using nitrogen sensitivity, is 6.2 μmol / g or more.
2. The zeolite membrane composite according to claim 1, wherein the zeolite is of the MFI type.
3. The zeolite membrane composite according to claim 1 or 2, wherein the Si / Al molar ratio of the zeolite membrane is 5.0 or more and 25.0 or less.
4. A method for producing a zeolite membrane composite, using a hydrothermal synthesis raw material mixture prepared by a method comprising: a first step of preparing a mixture containing at least aluminum atom raw materials, alkali metal atom raw materials, and water; a second step of mixing in silicon atom raw materials; a third step of heating the mixture after the second step to 40°C or higher; and a fourth step of mixing water with the mixture after heating in the third step.
5. The method for producing a zeolite membrane composite according to claim 4, wherein the water content of the mixture prepared by the first step is 30% or more and 80% or less of the water content of the hydrothermal synthesis raw material mixture.
6. A method for producing methanol, comprising reacting a raw material gas containing at least hydrogen, carbon monoxide and / or carbon dioxide in a reactor in the presence of a catalyst, wherein the methanol produced by the reaction is extracted by permeating through the zeolite membrane composite described in claim 1 or 2.
Citation Information
Patent Citations
Method for producing methanol
JP1997511509A
Reactor for producing methanol and method for producing methanol
JP2007055970A
Method of carrying out chemical equilibrium reaction using permselective membrane
JP2016117726A
Zeolite separation membrane and separation module
JP2016174996A